The archaeology of Yucatán : new directions and data - Stanton, Travis W., 1971- (Archaeopress pre-Columbian archaeology, 2014)
This volume was conceived to provide a forum for Mexican and foreign scholars to publish new data and interpretations on the archaeology of the northern Maya lowlands, specifically the State of Yucatán.